Ocena wiedzy studentów na temat zasad pielęgnacji cery = Evaluation of students' knowledge about skin care - Bojarczuk, Katarzyna Anna; Lewicki, Marcin; Michalczak, Magdalena; Smoleń, Agata (Journal of Education, Health and Sport, 2016)
Bojarczuk Katarzyna, Lewicki Marcin, Michalczak Magdalena, Smoleń Agata. Ocena wiedzy studentów na temat zasad pielęgnacji cery = Evaluation of students' knowledge about skin care. Journal of Education, Health and Sport. 2016;6(6):661-676. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60816 http://ojs.ukw.edu.pl/index.php/johs/article/view/3775 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.05.2016. Revised 25.06.2016. Accepted: 28.06.2016. Ocena wiedzy studentów na temat zasad pielęgnacji cery Evaluation of students' knowledge about skin care Katarzyna Anna Bojarczuk, Marcin Lewicki, Magdalena Michalczak, Agata Smoleń Katedra i Zakład Epidemiologii i Metodologii Badań Klinicznych Uniwersytetu Medycznego w Lublinie Słowa kluczowe: skóra; pielęgnacja cery; wiedza studentów. Key words: skin; skin care; knowledge of students. Abstrakt Wprowadzenie. Skóra pełni różnorodne funkcje, więc ważne jest poznanie i zrozumienie jej budowy oraz właściwości. Wiedza na jej temat stanowi podstawę do oceny stanu skóry i jej odpowiedniej pielęgnacji, dostosowanej do rodzaju, poszczególnych okoliczności i warunków życiowych. Cel pracy. Ocena wiedzy studentów na temat zasad pielęgnacji cery. Materiał i metody. Metodą badawczą były anonimowe badania ankietowe umożliwiające uzyskanie od respondentów danych o ich wiedzy na temat zasad pielęgnacji cery. W badaniu wzięło udział 210 studentów. Wyniki. Większość respondentów oceniło swoją cerę jako mieszaną – 39%. Najczęstszym problemem występującym u młodych dorosłych jest trądzik – 45%. Zdecydowana większość ankietowanych – 87% deklaruje codzienne dbanie o swoją cerę. Przy wyborze kosmetyków badani kierują się przede wszystkim cerą – 39%. Najczęściej stosowanym kremem jest krem nawilżający- 69%. Aż 96% respondentów posiada wiedzę na temat wpływu diety, nałogów oraz odpowiedniego nawodnienia na wygląd skóry, ale 32% nie stosuje kosmetyków zawierających filtry UV. Głównym źródłem źródłem informacji na temat kosmetyków pielęgnacyjnych dla badanych jest internet - 73%. Swoją wiedzę na temat prawidłowej pielęgnacji skóry jako dobrą ocenia 54% osób. Wnioski: 1. Większość ankietowanych dba o swoją cerę codziennie, stosując kosmetyki pielęgnacyjne do twarzy. 2. Najczęściej stosowanym kremem pielęgnacyjnym do twarzy wśród studentów jest krem nawilżający. 3. Używanie kosmetyków pielęgnacyjnych pozwala badanym przede wszystkim utrzymać dobry wygląd skóry oraz dobrze się czuć. 4. Większości badanych zwraca uwagę na swój wygląd zewnętrzny. 5. Internet jest dla studentów głównym źródłem wiedzy na temat kosmetyków pielęgnacyjnych. Abstract Background: The skin performs various functions, that is why it is crucial to understand its structure and properties. These information form the basis of skin condition evaluation and guidelines for proper skin care, adjusted in accordance with persons basic skin type, particular circumstances and living conditions. Objectives: Evaluation of students' knowledge about rules of skin care. Material and methods: Evaluation of students' knowledge concerning proper skin care guidelines was conducted among 210 students using anonymous survey. Results: Majority of respondents determined their skin type as a combination one – 39%. Acne is regarded as the most often occurring skin condition among young adults - 45%. Significant number of interviewees - 87% report performing daily skin care activities. The choice of skin care products is determined mainly by skin type - 39%. Moisturizing cream is among the most widely used cosmetic cream - 69%. As many as 96% of respondents have knowledge about the influence of diet, addictions, and adequate hydratation on skin appearance, yet 32% do not use cosmetics with UV filters. The main source of source of information on skin care for the test is the internet - 73%. Their knowledge about proper skin care as a good estimated 54%.